(untitled) (Research, Society and Development, 2022)
Obstructive Sleep Apnea and Hypopnea Syndrome (OSAHS) is a progressive disorder of the respiratory system that seriously affects the general health and, consequently, the quality of life of an individual. The aim of the present study was to report a case of moderate OSAHS treated with the supervised use of the Gradual Mandibular Advancement Intraoral Appliance (AIO). The treatment was followed up through the patient’s report, evaluation of the Epworth Sleepiness Scale, and its result was confirmed by the baseline polysomnography exam. After the treatment period, there was an improvement in the symptoms reported by the patient and in the polysomnographic parameters. The patient went from a moderate OSAHS condition, with an Apnea and Hypopnea Index (AHI) of 24.7 events per hour, to a mild condition with an AHI of 10.7 events per hour. Thus, it can be concluded based on the present case that the AIO was effective for the conservative treatment of moderate OSAHS.